Algunos enigmas de la especificidad lingüística común rumano-judeoespañola - Gabinsky, Marcos Alejandro (Revista de Filología Románica, 2009)
First, the article deals with some turns of speech of the Balkan Judeo-Spanish once explained erroneously without taking into account their Balkan origin (questions like Ké ke (f)aga? etc.), as well as, on the contrary, analogies with some Balkan languages which proved to be further evolutions of a Portuguese model (kale echo), some other facts still remaining to be explained: such as a number of phraseologic and syntactic phenomena peculiar in common not only to Balkan Judeo-Spanish and Romanian, but what is surprising, to the latter and the Moroccan hakitía.